2019
DOI: 10.1186/s40880-019-0411-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends and survival prediction of hepatoblastoma in children: a population‐based study

Abstract: BackgroundHepatoblastoma is a rare disease that nevertheless accounts for the majority of liver malignancies in children. Due to limited epidemiological data, therapy for hepatoblastoma tends to be individualized. This study aimed to evaluate incidence trends of hepatoblastoma and to develop a nomogram to predict the survival of children with newly diagnosed hepatoblastoma on a population-based level.MethodsIndividuals up to 18 years of age with hepatoblastoma recorded in 18 registries of the Surveillance, Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 34 publications
12
101
2
1
Order By: Relevance
“…While HB incidence rates were stable over nine years from 2001 onwards among children aged <20 in the USA, 29 another USA-based study reported that longer-term trends increased among this age group. 38 Long-term trends among ages 0-14 years also increased in Canada, 30 Germany, 39 and Taiwan 40 over recent decades (from around the mid-1990s-2012). However, two other studies reported stable trends for this age group from 1983 to 2007 in Spain 35 and 1976 to 2011 in Italy.…”
Section: Hepatoblastomamentioning
confidence: 99%
“…While HB incidence rates were stable over nine years from 2001 onwards among children aged <20 in the USA, 29 another USA-based study reported that longer-term trends increased among this age group. 38 Long-term trends among ages 0-14 years also increased in Canada, 30 Germany, 39 and Taiwan 40 over recent decades (from around the mid-1990s-2012). However, two other studies reported stable trends for this age group from 1983 to 2007 in Spain 35 and 1976 to 2011 in Italy.…”
Section: Hepatoblastomamentioning
confidence: 99%
“…Of 150 total HCC cases recorded during 2004-2015, 80 were treated surgically [14]. Twenty In reviews of the SEER database, HB incidence increased significantly between 2004 and 2015 (annual percentage change, 2.2%; 95% confidence interval (CI) 0.5% to 3.8%, p < 0.05) [13]. In particular, this increase was observed among 2-to 4-year-old patients, males, and African-Americans.…”
Section: Changing Tumor Incidence and Use Of Liver Transplantation Fomentioning
confidence: 99%
“…Reports based on the SEER registry have compared outcomes after surgical resection and LT, while those based on the SRTR database have described outcomes after LT for all liver cancers by era, and the effect of systemic changes on these outcomes [13][14][15][16][17]70]. These changes include assigning higher model-for-end-stage-liver-disease (MELD) or pediatric end-stage-liver-disease (PELD) scores for these tumors since 2010, the addition of doxorubicin and other agents to cisplatin-based COG protocols, AHEP-0731 (2009), and the use of PLADO with sorafenib for HCC (2007) [70].…”
Section: Hepatoblastomamentioning
confidence: 99%
“…The age-standardized incidence of GBC was expressed as per 100,000 individuals using the 2000 US Standard Population. Annual percentage change (APC) in the incidence was calculated using the weighted least squares method 16 . Statistical analysis was conducted using R software 3.6.2 (R foundation, Vienna, Austria) and SPSS version 21.0 (SPSS Inc., Chicago, IL, USA).…”
Section: Nomogram Development and Statistical Analysesmentioning
confidence: 99%